Static and dynamic impacts of emergency generator in distribution systems - Nurashikin, Mamat (2009)
Nowadays, most of the people in this world cannot live without electricity especially to the patient at the hospital. Emergency power system is to improve power quality in delivering the electrical power to the customers. The utility company is responsible to locate emergency power system such as emergency generator. This project will presents the impacts of static and dynamic of emergency generator when it has been allocated in distribution systems. Static means the load flow and fault analysis while dynamic is transient stability analysis. 4-bus test system and 9-bus test system will be analyzed using PSCAD and MATLAB programs. The data of two test system are obtained from MATPOWER. The synchronous machine with exciter and governor model used as emergency generator. Critical loads are connected with the emergency generator. From the result, load flow was varied after an emergency generator placement. The real power is increase while reactive power is decrease during the switching caused by circuit breaker. It has a fault current when fault occurred in the system. Fault is setting in duration of 0.2s at 1.0s of time. Circuit breaker is opened to interrupt the circuit and isolate the fault in the system and close back after the fault is cleared. An emergency generator is supplied the voltage to critical load during the fault event. When fault occurred, it only gives the impacts to the line and the bus during the fault. Load angle of generator is experience to transient stability. Before fault occurs, it is in steady-state condition. Transient stability conditions occur after fault is clear then become in stability condition. For the conclusion, transient stability is not affected in distributing electricity to the customer. By placing an emergency generator, it has no problem in order to distribute energy to the load either in normal condition or abnormal condition.